PENGEMBANGAN E-MODUL P5RA BERBASIS ECO-CULTURE BLITAR PADA PELAJARAN IPAS DI MADRASAH IBTIDAIYAH - Rya Nika Dilava; Surayanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The lack of integration of local wisdom in science learning and the use of learning resources that are still centered on textbooks have an impact on students' low understanding of local wisdom in their surroundings. This study aims to develop a P5RA e-module based on Blitar eco-culture in science lessons at Madrasah Ibtidaiyah. The research method used is R&D through the ADDIE model which covers the analysis, design, development, implementation, and evaluation phases. The research trial subjects included 28 fourth-grade students of MI Perwanida. Data collection techniques were carried out using interviews, questionnaires, observations, and learning outcome tests. The research findings indicate the validation of the e-module for the very valid category with a percentage of assessments from material experts of 90.51%, media experts of 95.45%, and instrument experts of 91.65%. The practicality of the e-module is categorized as very practical from the responses of teachers of 88.7% and students of 91.3%. The effectiveness of the e-module is shown by the difference between the pretest and posttest with a significance of 0.000 and an N-Gain of 78.97% in the effective category. Thus, the e-module can be used as a teaching material in supporting science learning in Madrasah Ibtidaiyah.